81.5k views
2 votes
(x + 12)2 + (y+13)2 = 36

What’s the steps to get the center and the radius?

1 Answer

5 votes

Explanation:


{(x + 12)}^(2) + {(y + 13)}^(2) = 36 \\ {(x + 12)}^(2) + {(y + 13)}^(2) = {6}^(2) \\ equating \: it \: with \: \\ {(x - h)}^(2) + {(y - k)}^(2) = {r}^(2) \\ - h = 12 \implies \: h = - 12 \\ - k= 13 \implies \: k = - 13 \\ \therefore \: center \: = (h, \: \: k) = ( - 12, \: \: - 13) \\ \: \: \: \: {r}^(2) = {6}^(2) \implies \: radius \: (r)= 6 \: units

User MacroMan
by
6.1k points